2012
DOI: 10.1108/01435121211279894
|View full text |Cite
|
Sign up to set email alerts
|

E‐textbooks usage by students at Andrews University

Abstract: Purpose -This study aims at identifying Andrews University's students' perceptions, behavior, use, and attitudes towards e-textbook and e-books in general. Design/methodology/approach -In the Fall semester of 2001-2012, Andrews University's bookstore offered 74 e-textbooks for purchase. The teachers who had the opportunity of using these e-textbooks for their classes were asked to distribute two questionnaires to their students: one to those who chose to buy and use the e-textbook and a slightly different one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 46 publications
0
9
0
3
Order By: Relevance
“…However, the such statements should be made carefully because it is not possible to give an unambiguous answer to the question of whether students prefer printed or electronic sources. There are still many students who prefer printed sources (Boumarafi, 2010;De Oliveira, 2012;Hamade & Al-Yousef, 2010;Hussain & Abalkhail, 2013;Rockinson-Szapkiw, Courduff, Carter, & Bennett, 2013;Shepperd, Grace, & Koch, 2008;Shuling, 2007;Swain, 2010;Woody, Daniel, & Baker, 2010). One of the reasons why students report that printed sources, such as books, have a better reputation and contain more basic and well established facts is that the Internet holds a great deal of irrelevant and inaccurate information that makes the search difficult (Griffiths & Brophy, 2005;Nkomo, Ocholla, & Jacobs, 2011;Ozoemelem, 2009;Sujatha & Mudhol, 2008;Wu & Chen, 2012;Yu-Mei & Artero, 2005).…”
Section: Students' Perceptions Of Electronic Resourcesmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the such statements should be made carefully because it is not possible to give an unambiguous answer to the question of whether students prefer printed or electronic sources. There are still many students who prefer printed sources (Boumarafi, 2010;De Oliveira, 2012;Hamade & Al-Yousef, 2010;Hussain & Abalkhail, 2013;Rockinson-Szapkiw, Courduff, Carter, & Bennett, 2013;Shepperd, Grace, & Koch, 2008;Shuling, 2007;Swain, 2010;Woody, Daniel, & Baker, 2010). One of the reasons why students report that printed sources, such as books, have a better reputation and contain more basic and well established facts is that the Internet holds a great deal of irrelevant and inaccurate information that makes the search difficult (Griffiths & Brophy, 2005;Nkomo, Ocholla, & Jacobs, 2011;Ozoemelem, 2009;Sujatha & Mudhol, 2008;Wu & Chen, 2012;Yu-Mei & Artero, 2005).…”
Section: Students' Perceptions Of Electronic Resourcesmentioning
confidence: 95%
“…The results of some studies suggest that students prefer e-journals, but at the same time they read more printed books than e-books (Grosch, 2012;Woo, 2005). As a significant disadvantage of electronic resources, students point out the feeling of fatigue when reading such materials from the computer screen and the inability to complete the experience that can be provided by leafing through printed books (De Oliveira, 2012;Liu, 2006;Shelburne, 2009;Shuling, 2007;Wu & Chen, 2012). Therefore, it is common practice to print out electronic documents, primarily for texts that require reading comprehension, not just a cursory browse (Hernon et al, 2007;Ji, Michaels, & Waterman, 2014;Liu, 2006).…”
Section: Students' Perceptions Of Electronic Resourcesmentioning
confidence: 96%
“…It could be localized or customized for a variety of learners, whether in different cultures or at different levels of education" (Matkin, 2009: p. 3). Despite the abovementioned benefits, the adoption of digital textbooks has reportedly been much slower than anticipated (Allen, 2008a;Guthrie, 2012;Lee, 2010;Oliveira, 2012;Thomas, 2007). The reasons for this slow adoption vary, but 3 principal reasons emerge from literature.…”
Section: Introductionmentioning
confidence: 99%
“…The reading trends of the 21st century are now beginning to leave textbooks and start heading to electronic books (e-books). A person's interest in gadgets and the internet is part of the growing population of e-book readers in the world [1], [2]. Annie & Duggan reported that the number of people reading e-books increased from 16% for Americans aged 16 and to 23% for those who were older [3].…”
Section: Introductionmentioning
confidence: 99%